Based Learning Media Model Website for Making Mood Boards Fashion at Vocational Education Institute - Ahsan, Rizka Sarah Heydarina Fathimah; Nurhadi, Didik; Nurjanah, Nunung (BRILIANT: Jurnal Riset dan Konseptual, 2023)
The research was conducted to design a learning media model that can be used online. The method in this study uses a 4D development model, a stage that is carried out only to the development stage. The application used to design learning media is Dreamweaver and then the qualification test is carried out by media experts and material experts and the trial test is done on 35 trainees in training institutions and courses. The resulting learning media model has qualifications in terms of usability, functionality, and visual communications aspects by media experts in highly qualified categories, and the qualification results by material experts in relation to learning design, material content, language, and communications things are obtained in the category Highly qualified, and evaluations by students of the results based on usability aspects in most of these applications are acceptable to students with highly satisfactory answers on components P1 to P10 with highly qualifying categories.